Bibliometric analysis of the Top 1000 most-cited articles in otolaryngology over the past decade: global research trends and hotspots - Wang, Zhipeng; Yu, Guodong (Frontiers in Surgery, 2025)
BackgroundThe field of otolaryngology has achieved remarkable progress over the past decade due to technological advancements and interdisciplinary integration. Understanding research trends and hotspots is essential to drive further innovation and development.MethodsA comprehensive search was conducted on Web of Science on November 22, 2024, to identify the top 1,000 most-cited otolaryngology publications from 2014 to 2024. Data were analyzed using GraphPad Prism v8.0.2, CiteSpace (6.2.4R), and VOSviewer (1.6.18) to visualize trends and research networks.ResultsThe annual publication volume in otolaryngology decreased after 2014, with the United States dominating in both publication count and citation frequency. Influential journals and prominent authors were identified, and research areas expanded beyond traditional clinical management to interdisciplinary fields. Chronic rhinosinusitis, olfactory dysfunction, and machine learning emerged as key research hotspots.ConclusionOtolaryngology has made significant progress across multiple domains. Future research should focus on integrating artificial intelligence into clinical practice, fostering interdisciplinary collaborations, and advancing precision medicine and translational research. These efforts will be critical for addressing emerging challenges and capitalizing on new opportunities in the field.